Linewidth Reduction by Feedforward Locking a Laser Diode to a Femtosecond Comb Line - Ziping Zhang; Yitang Dai; Pan Ou; Feifei Yin; Yue Zhou; Jianqiang Li; Kun Xu (IEEE Photonics Journal)
We propose and demonstrate a novel method to narrow the linewidth of a laser diode at 1550 nm by an electronics-assisted feedforward path and weak locking to a femtosecond comb line simultaneously. By using a femtosecond comb as an ideal ultranarrow-linewidth optical reference, the laser diode is down converted, and its phase noise is “recorded” by the resulted intermediate frequency tone, which is filtered by a 40-MHz electronic filter. The consequentially introduced electronic delay is designed to match the optical delay, which is experienced by the same laser diode for upconversion. The delay match ensures that the phase noise of laser diode can be counteracted by its former “record” in upconversion and realizes linewidth reduction. As a result, the 20-dB linewidth of final radiation has been measured as 26 kHz, which is 1/35 of that of the laser diode.